Claudine at St. Clare's - Blyton, Enid (Egmont UK Ltd, 1944)
Another term is off to a cracking start. New girl Claudine-Mam'zelle's niece!-causes chaos and hilarity with her determination to bend the rules. Just how long will she last at St. Clare's?...
Keywords: Juvenile Fiction / Adventure